Influence of cholecalciferol (Vitamin D3) on the course of experimental systemic lupus erythematosus in F1 (NZBxW) mice - Vaisberg, Mauro W.; Kaneno, Ramon [UNESP]; Franco, Marcelo F.; Mendes, Nelson F. (Wiley, 2000)
The course of systemic lupus erythematosus (SLE), an autoimmune disease, is markedly affected by hormones such as estrogen and prolactin. It is well known that heavy exposure to sunlight has deleterious effects on SLE, triggering episodes of the disease. Classical explanations for this occurrence suggest that UV radiation damages DNA, which becomes immunogenic, or induces exposure of the Ro antigen in keratinocytes. In recent years, it has been shown that vitamin D3 has important effects on the immune system. Thus, we proposed an alternative hypothesis, suggesting that UV radiation, by promoting vitamin D3 synthesis, could be a factor aggravating the course of SLE after exposure to sunlight. To test this hypothesis, we injected F1(NZBxW) mice, which are prone to developing SLE, with vitamin D3, and we demonstrated a worsening of the histopathological findings in the kidney. (C) 2000 Wiley-Liss, Inc.
Keywords: Autoimmune disease; Hormones; Lupus nephritis; Ultraviolet radiation; Vitamin D3; colecalciferol; animal experiment; animal model; autoimmune disease; controlled study; disease course; histopathology; immunopathogenesis; lupus erythematosus nephritis; mouse; sunlight; systemic lupus erythematosus; ultraviolet radiation; Antibodies, Antinuclear; Cholecalciferol; Disease Progression; Immune System; Kidney Glomerulus; Lupus Erythematosus, Systemic; Lupus Nephritis; Mice, Inbred NZB; Severity of Illness Index; Sunlight; Ultraviolet Rays; Animalia